Plant–soil feedback from eastern redcedar (Juniperus virginiana) inhibits the growth of grasses in encroaching range. Issue 10 (17th October 2022) - Bennion, Leland D.; Ward, David
Abstract: The encroachment of woody plants into grasslands is an ongoing global problem that is largely attributed to anthropogenic factors such as climate change and land management practices. Determining the mechanisms that drive successful encroachment is a critical step towards planning restoration and long‐term management strategies. Feedbacks between soil and aboveground communities can have a large influence on the fitness of plants and must be considered as potentially important drivers for woody encroachment. We conducted a plant–soil feedback experiment in a greenhouse between eastern redcedar Juniperus virginiana and four common North American prairie grass species. We assessed how soils that had been occupied by redcedar, a pervasive woody encroacher in the Great Plains of North America, affected the growth of Andropogon gerardi, Schizachyrium scoparium, Bromus inermis, and Pascopyrum smithii over time. We evaluated the effect of redcedar on grass performance by comparing the height and biomass of individuals that were grown in live or sterilized conspecific or redcedar soil. We found redcedar created a negative plant–soil feedback that limited the growth of the cool season grasses B. inermis and P. smithii, reducing their overall biomass by >60%. These effects were found in both live and sterilized redcedar soils. In live soils, some growth suppression can be attributed to the negative effects of soil microbes. The limitation of grass growth in sterile soils indicates redcedar may exude an allelochemical into the soil that limits grass growth. Our results demonstrate that plant–soil feedback created by redcedar inhibits the growth of certain grass species. By creating a plant–plant interaction that negatively affects competitors, redcedars increase the probability of seedling survival until they can grow to overtop their neighbors. These results indicate plant–soil feedback is a mechanism of native woody plant encroachment which could be important in many systems yet is understudied. Abstract : The alteration of the near soil environment by plants, deemed plant–soil feedback, can have differential effects on conspecific and heterospecific plants and is a process that has been identified as an important contributor to the success of range‐expanding species. Using an experimental approach, we demonstrate that eastern redcedar ( Juniperus virginiana ), a widespread conifer that is encroaching into the grasslands of eastern North America, creates a plant–soil feedback that suppresses the growth of common prairie grasses. This suppressive effect could provide a crucial driver for the success of eastern redcedar establishment in highly competitive prairie plant communities.